PROBLEMS OF ENSURING THE PROCEDURAL INDEPENDENCE OF THE INVESTIGATOR IN THE PRE-TRIAL INVESTIGATION SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Pardayev , Elbek (Journal of Research and Development, 2026)
The article examines the problem of ensuring the procedural independence of investigators and inquiry officers within the criminal justice system of the Republic of Uzbekistan. Based on a systematic analysis of legislation, empirical sociological research, and a review of law enforcement practice, the study identifies institutional factors that constrain the genuine autonomy of investigative personnel. It demonstrates that the formally enshrined guarantees of independence are largely declarative in nature and are not supported by effective enforcement mechanisms. The research establishes that the dominant position of the prosecutor’s office, the hierarchical departmental structure of investigative bodies, the emphasis on statistical performance indicators, and the career-related dependency of personnel significantly influence procedural decision-making. Survey findings confirm the existence of systematic interference in the course of investigations, which adversely affects the proper legal classification of crimes and compliance with procedural time limits. The article substantiates the need for comprehensive institutional reforms, including strengthening the legal status of investigators and redistributing procedural powers within the pre-trial investigation framework.